Pemakanan menurut perspektif fiqh al-Hadith: Kajian terhadap pengusaha produk makanan / Siti Sarah Izham - Siti Sarah , Izham (2018)
The awareness among Malaysians on the importance and benefits of taking food according to the Sunnah of the Prophet p.b.u.h, better known as “sunnah food” is currently very high. Companies that are producing sunnah-based food have been emerging rapidly. The question is, are the ingredients alone sufficient for a product to be labelled as “sunnah food”? The circular of Malaysian Halal Certification, number 2 year 2016 by JAKIM, one of the mentioned aspects is the prohibition of labeling the product with "sunnah food. The objectives of this study are to elucidate matters pertaining to diet from the hadith perspective, to analyse hadiths relating to diet in the al-Ṣaḥīḥaīn and sharḥ works, to present explicit dietary principles from the fiqh al-Hadith discussions, to analyse the food production practices by the food product entrepreneur Sidratul Cooperation and compare them to dietary principle according to the fiqh al-ḥadith and to develop a proposal for dietary guidelines according to the Prophetic perspective. This is a qualitative study, where the data collection involves library research and field research, namely observation and thorough interviews. Interviews were conducted with all the staff of Sidratul Cooperation. The collected data were analysed through the inductive and deductive methods, content analysis method and comparative study. The results of the analysis reveal that from the 413 hadith in the al-Ṣaḥīḥaīn, six aspects can be extracted which are adab (ethics), ingredients, combination (of ingredients), ruling, management and narrative involving diet. However, based on the discussion in fiqh al-ḥadith, there are 18 dietary principles. The analysis on the food production practices by Sidratul Cooperation reveals that in terms of adab, the company practices all of the principles except postproduction recitation. In terms of ingredients, the consistency of the ingredients used is vi based on the principles of ingredients, except for manna. For the authenticity of a particular ingredient, the company is very meticulous as they do not only depend on the certificate of analysis (COA) and certificate of origin (COO), but would carry out further tests in other labs. In terms of combining the ingredients, the company combine between various ingredients in one respective product. In terms of ruling, the understanding of halal and ṭayyib and the application in the production is based on the guidelines by JAKIM and IMP. In terms of management, the company places importance on the hiring of the production workers and is careful when it comes to aspects of hygiene, water source, equipment and the workers themselves. The finding of this research to develop a component guideline for dietary based on the understanding of the Prophet’s.